2019
DOI: 10.1111/clr.474_13509
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a workflow using sleeveless 3D printed surgical guides made from a cost‐effective and biodegradable material: An in vitro study

Abstract: Background : Digital implant planning and guided insertion facilitates prosthetically-driven implant positioning. Nowadays, most guide systems are using photopolymerized 3D printed surgical templates with metal sleeves for drill guidance. However, a cost-effective but accurate alternative might be represented by sleeveless surgical guides made of polylactate. Since absence of wear cannot be secured using sleeveless surgical guides, this biodegradable material could be beneficial.Aim/Hypothesis : To determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…These results are in agreement with Pieralli et al2020 [18] which concluded that Comparable levels of accuracy in implant placement were achieved when utilizing FDM and SLA printed surgical guides This coincides with Hromadnik et al 2020 [19] which reported that when comparing the four evaluated groups (SLA-S, SLA-NS, FDM-S, FDM-NS), no statistically significant differences regarding to the implant site were found.…”
Section: Discussionsupporting
confidence: 89%
“…These results are in agreement with Pieralli et al2020 [18] which concluded that Comparable levels of accuracy in implant placement were achieved when utilizing FDM and SLA printed surgical guides This coincides with Hromadnik et al 2020 [19] which reported that when comparing the four evaluated groups (SLA-S, SLA-NS, FDM-S, FDM-NS), no statistically significant differences regarding to the implant site were found.…”
Section: Discussionsupporting
confidence: 89%
“…Studies that compared the accuracy of implant placement in relation to the pre-planned implant positions with the use of surgical guides commonly used surgical guides that required metal sleeve insertion; industrial 3D printers were used to fabricate the body of the surgical guides, and the metal sleeves were inserted [ 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. As in-office 3D printers are becoming more popular and their accuracy is being reported as comparable to that of industrial printers, metal sleeveless surgical guides are becoming a major trend [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Visors can be manufactured from several types of materials that include polycarbonate, propionate, acetate, poly(vinylchloride), and PETG [9]. Since PLA and PETG are known to show volume change during sterilization processes [21], one-time use of the visor is recommended, whereas a study showed that sterilized 3-D printed surgical splints using filaments based on lignin (Green-TEC Pro) remained dimensionally stable [22]. The sterilization of the frame might be possible, but was not tested in this study.…”
Section: Materials Selectionmentioning
confidence: 99%